What Persuades College Students to Take That First Sip? - A Study on The Influence of Society and Media on Attitude Towards Alcohol Consumption - Elangovan, Venmathi; Nirupama , AY; Ravivarman G, (National Journal of Community Medicine, 2022)
Background: According to WHO statistics, close to 3 million deaths occur every year due to harmful use of alcohol of which 3.2 lakh people are aged between 15-29 years. College students are more prone to experimenting and risk taking behavior. Keeping this in mind, our study was aimed to assess the alcohol use patterns and factors associated with alcohol consumption among college students. Methodology: A cross-sectional study was conducted including college students from various streams in the South Indian states of Kerala and Tamil Nadu. Data was collected from 1129 participants using a self-administered questionnaire consisting of 4 sections including socio-demographic details, alcohol use patterns, attitude towards alcohol consumption and media exposure. Results: Prevalence of alcohol consumption in the sample population was found to be 31% (348). Among the 348, 30.2% (105) reported that one of the reasons for the consumption of the first drink of alcohol was peer-pressure. Higher prevalence of alcohol consumption seen among the groups with higher media exposure and higher tolerance to alcohol advertising was found to be statistically significant. The study statistics show that 600(53.14%) participants were exposed to actors consuming alcohol in media more than 10 times in the past 30 days while only 320(28.34%) reported seeing warnings or health education material in the same duration. Conclusion: Considering the above findings, it is high time policy makers focused on using media for health promotion and health education, since it is proving to have the potential to influence the decisions and lifestyles of the future generations.